PENGUATAN MENTALITAS KARYAWAN DALAM MENGHADAPI PERENCANAAN PERUBAHAN ORGANISASI DARI WILAYAH OPERASIONAL PROVINSI KEPADA NASIONAL (Penelitian Kualitatif Studi Kasus pada Lembaga Keuangan Mikro Syari’ah BMT Mitra Umat Pekalongan) - Arif Budiharjo (LPPM Universitas Pekalongan, 2022)
This study has the aim of analyzing qualitatively the phenomena or symptoms that occur at the BMT Mitra Ummah Pekalongan Syariah Microfinance Institution, and how the institution anticipates, and conceptually formulates solutions related to the planning and implementation process of organizational changes that are being undertaken to change from business and organizational coverage with the province of Central Java leading to Indonesian or national operational areas. Regarding the organizational changes or the scope of business, this study focuses more on the aspect of mental readiness of its employees, as well as how to build mental readiness in order to provide smoothness for the